Entrepreneurship, investment, and spatial dynamics : lessons and implications for the enlarged EU - Nijkamp, Peter; Moomaw, Ronald L.; Traistaru-Siedscchlag, Iulia (Cheltenham, UK ; Northampton, Mass. : E. Elgar Pub., 2006)
This book offers empirical new evidence regarding the spatial dimension of investment, entrepreneurship and knowledge spillovers, and features both individual and cross-country analyses.
Includes bibliographical references and index.
gau 20/06/14
Loans
Keywords: Entrepreneurship -- European Union countries; Investments -- European Union countries; European Union countries -- Economic conditions -- Regional disparities; European Union countries -- Economic integration